“THE MISSION” STRATEGY APPLICATION TO ELEVATE STUDENTS’ SPEAKING PERFORMANCE - Suhria Suhria; Amaluddin Amaluddin; Siti Hajar Larekeng (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
The English Department students of Muhammadiyah University of Parepare faced some difficulties in performing speaking. For instance, the students feel anxious and worried about making mistakes, and they lack language and communicative knowledge. Therefore, to help students overcome their problems and enhance their communicative competence, this research was conducted to determine whether applying “The Mission” strategy could elevate English Education Department students' speaking performance. The researcher in this study conducted a pre-experimental method. The population was the first semester of English Department Students. The researcher used the total sampling method in deciding the research sample. The instruments used in collecting the data were informal interview tests, also known as “Question and Answer”. The result of the data found was analysed by using SPSS Application. The results of the research showed that the students’ speaking performance after giving treatment was significantly improved. It was proved by the data of the students’ mean score post-test was higher than in pre-test (77,00 37,77). It indicates that the elaboration of Task-based Instruction with “The Mission” strategy can empower students’ in performing speaking.